Sustainable human resource management practices in organizational performance: The mediating impacts of knowledge management and work engagement - Shatha Abu-Mahfouz; Mutia Sobihah Abd Halim; Ayu Suriawaty Bahkia; Noryati Alias, Ph.D. in Management; Abdul Malek Tambi (Journal of Entrepreneurship, Management and Innovation, 2023)
PURPOSE: Modern business and global organizations are regularly presented with challenges caused by unpredictable competitive environments. Human resource management (HRM) practices give sustainable opportunities for employees to use their abilities and express their enthusiasm to obtain skills and knowledge and to apply them at the workplace with a view to achieving engaged individuals and increasing organizational performance. This article presents a recent study outcome to examine (i) the mediating role of knowledge management and work engagement and (ii) the effect of sustainable HRM practices on organizational performance. METHODOLOGY: 500 self-reported questionnaires were distributed to Jordanian university lecturers (research population) for data collection. The study data were assessed with structural equation modeling (SEM) using IBM-SPSS-AMOS 25.0. FINDINGS: Two pivotal outcomes were identified: (i) sustainable HRM practices, knowledge management, and work engagement were positively associated with organizational performance; (ii) knowledge management and work engagement played a mediating role in the sustainable HRM practice-organizational performance correlation. IMPLICATIONS: Overall, employee cooperation proved essential to optimize organizational performance, specifically during their engagement in sustainable HRM practices and knowledge management. Finally, the research proposed several practical recommendations and interventions on sustainable HRM for future research. ORIGINALITY AND VALUE: The research has provided proof of five variable relationships contained in the model. Firstly, organizational performance increased with sustainable HRM practices through knowledge management. Secondly, organizational performance increased with sustainable HRM practices through work engagement. Thirdly, work engagement increased with sustainable HRM through knowledge management. Fourthly, organizational performance increased with knowledge management through work engagement. Fifthly, organizational performance increased with sustainable HRM through knowledge management and work engagement.